ANALISIS PERANAN KOPERASI DALAM MENINGKATKAN KESEJAHTERAAN ANGGOTA DAN MASYARAKAT DI SEKITAR WILAYAH SUKAMAJU BARU TAPOS DEPOK - Ridhowati Ridhowati; Syafa’atun Syafa’atun; Nurlaela Nurlaela (Sekolah Tinggi Pariwisata Mataram, 2023)
Cooperatives are a collection of people who have common goals or interests so that cooperatives can be said to be the formation of a group of people who have common goals. This group will become members of the cooperative he founded. Based on library data and field research results, this research can be concluded as follows: The existence of the Mandiri Zayda Cooperative can increase the economic income of each member. The existence of the Zayda Mandiri Cooperative increases the income of its members, by sharing the remaining business results (RBR). The existence of the Zayda Independent Cooperative Offering goods and services at lower prices